2007
DOI: 10.1016/j.neuroscience.2007.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Task specific influences of Parkinson’s disease on the striato-thalamo-cortical and cerebello-thalamo-cortical motor circuitries

Abstract: The motor deficits in Parkinson's disease (PD) have been primarily associated with internally guided (IG), but not externally guided (EG), tasks. This study investigated the functional mechanisms underlying this phenomenon using genetically-matched twins. Functional magnetic resonance images were obtained from a monozygotic twin pair discordant for clinical PD. Single-photon emission computed tomography neuroimaging using [(123)I](-)-2-beta-carboxymethoxy-3-beta-(4-iodophenyl)tropane confirmed their disease-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 37 publications
7
92
2
2
Order By: Relevance
“…Consequently, these produce enhancement of the neural processing mechanisms required for proper task performance [45,46]. This comes in agreement with Wright and Shea [47] who concluded that attention is critical for the development of motor control.…”
Section: Discussionsupporting
confidence: 80%
“…Consequently, these produce enhancement of the neural processing mechanisms required for proper task performance [45,46]. This comes in agreement with Wright and Shea [47] who concluded that attention is critical for the development of motor control.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the thalamus [39] and the globus pallidus [40] were, according to our first hypothesis, also activated after ACUP on GB 34; however, this was only the case in healthy participants. More specifically, in healthy participants, it was found that almost all brain activation occurred in the basal ganglia.…”
Section: Discussionmentioning
confidence: 62%
“…However, it remains unclear why the effect of acupuncture on GB 34 is visible in the prefrontal cortex and precentral gyrus and not in the thalamus, globus pallidus, and caudate, which are areas that are also known to be affected by PD [38,39,41]. In previous studies [63,65], it was found that the prefrontal cortex and precentral gyrus were impaired in patients with PD when conducting motor tasks and that these areas are related to motor function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regions examined included bilateral caudate, lentiform nucleus, thalamus, supplementary motor area (SMA), primary motor cortex (PMC), prefrontal cortex (PFC), and cerebellar hemisphere. We note that the rater reliability of the drawn ROIs was demonstrated in an earlier publication [20] by the high degree of correlation between the segmentations of the same ROIs extracted twice, once predrug and once postdrug administration on a pair of twins, one of whom has Parkinson's disease (PD).…”
Section: Fmri Preprocessing and Statistical Map Generationmentioning
confidence: 88%